Missed opportunities for venous thromboembolism prophylaxis during pregnancy and the postpartum period: evidence from mainland China in 2019 - Zhekun Zhao; Qiongjie Zhou; Xiaotian Li (BMC, 2021)
Abstract Background Venous thromboembolism (VTE) has become one of the leading causes of maternal mortality. Thromboprophylaxis is recommended for the prevention of this condition; however, its use appears to be insufficient. Therefore, in this study, we aimed to identify the missed opportunities for VTE prophylaxis in hospitals that provide maternal healthcare in mainland China. Methods In this cross-sectional survey-based study, we collected case data on pregnant and puerperal women with deep vein thrombosis and pulmonary thromboembolism from January 1st to December 31st, 2019. Demographics, obstetric information, VTE risk assessment scores, and prophylaxis-related information were recorded. Thromboprophylaxis included mobilization, mechanical methods, and treatment with anticoagulants. Results Data corresponding to a total of 106 cases from 26 hospitals across China were collected, and 100 (94.3%) cases, 75 cases involving deep vein thrombosis and 25 cases involving pulmonary thromboembolism, were included in the final analysis. VTE occurred in 80% of the patients at the postpartum stage, while 20 patients developed the disease during the antenatal stage. Cesarean section, advanced maternal age, and obesity were the most common risk factors related to VTE during the postpartum stage, while a previous VTE-related history was a prominent risk factor among antenatal cases. Up to 75% of the patients had one or more missed opportunities for prophylaxis. The lack of the implementation of mechanical methods (60.8% vs. 24.5%, P < 0.001) and anticoagulant treatment (61.1% vs. 48.7%, P < 0.001) were more common in general hospitals compared to those of specialized hospitals. In women assessed as high-risk, anticoagulant treatment was lacking in 41 (54.7%) cases. More importantly, the lack of the implementation of mechanical methods was more common among women assessed as low-risk (56.0% vs. 38.7%, P < 0.001). Among the antenatal cases, the lack of treatment with anticoagulants (100.0% vs. 48.5%, P < 0.001) and implementation of mechanical methods (70.0% vs. 36.7%, P < 0.001) was highlighted. In addition, the lack of early mobilization was much more prominent among the PTE cases (10.5% vs. 37.5%, P < 0.001). Conclusions At least one prophylactic opportunity was missed in most of the enrolled Chinese women with VTE during the course of their maternal healthcare. Missed prophylactic opportunities varied with the type of hospitals, risk assessment, onset timing and disease type. Further efforts from patients, healthcare systems, and healthcare providers are needed for improving the implementation of preventative strategies.